Species diversity, species similarity and shared species of understorey birds at mount Jagoi and mount Singai, Bau, Sarawak - Cheng, Poh Leng (Universiti Malaysia Sarawak, UNIMAS, 2012)
Birds are useful in indicating the forest’s vegetation and they are important for environmental monitoring. This study focuses on the understory bird community at Mount Jagoi and Mount Singai in Bau, Sarawak in terms of species diversity, species similarity and shared species. Birds at Mount Jagoi were captured by mist-netting from 8th to 12th August, 2011, 8th to 12th November, 2011, and 2nd to 6th February, 2012. A total of 298 individuals comprising 53 species from 22 families were recorded at Mount Jagoi; while there were 127 individuals comprising 26 species from 12 families were documented at Mount Singai. The most dominant species in both areas was Little Spiderhunter (Arachnothera longirostra); while the dominant families recorded were Pycnonotidae and Timaliidae. The results showed that bird community at Mount Jagoi was richer and significantly more diverse than Mount Singai, but they were having high similarity of bird’s composition. Mount Jagoi and Mount Singai shared 19 bird species based on available data, where more than 70% of bird species at Mount Singai are present at Mount Jagoi. This may be resulted from similar habitat and food sources at both areas. The prediction analyses showed that 32 species should be shared between the two mountains; and for further survey of 300 individuals, 10 new species should be discovered at both mountains.